Cushingoid Features in an Obese Female with XY Karyotype - Garg, Gunjan; Gogia, Atul; Kakar, Atul (Journal of the ASEAN Federation of Endocrine Societies, 2014)
Disorders of sexual development are congenital in nature. Complete androgen insensitivity syndrome (CAIS) is a rare disorder with an incidence of nearly 1 in 20,000 male births. The majority of patients present with complaints of primary amenorrhoea and are phenotypically female but genotypically male. We report a case of a 40-year-old female presenting with backache and skin ulcers who was found to have exogenous Cushing’s syndrome with long glucocorticoid administration and suspected CAIS. The ulcers were secondary to intramuscular pentazocine injections.